Examining zoonotic notifications in Aboriginal and Torres Strait Islander populations over time: An analysis of the National Notifiable Diseases Surveillance System from 1996-2021 - Tamara Riley; Raymond Lovett; Neil E. Anderson; Anna Meredith; Bonny Cumming; Joanne Thandrayen (Australian and New Zealand Journal of Public Health)
Objective: This paper utilised the National Notifiable Diseases Surveillance System database to analyse the commonly notified zoonotic disease presentations in Aboriginal and Torres Strait Islander populations over 25 years, from 1996-2021. Methods: We analysed the top four zoonotic notifications using a descriptive analysis, a time series analysis assessing the trends and seasonal indices, and a de-seasonalised analysis to assess the years contributing to an increase above the trend. Results: Results show an increase in notifications for salmonellosis and campylobacteriosis over the last 10 years. On average, all diseases saw an increase in notifications above the trend in Q1 (Jan-Mar) and less so Q2 (Apr-Jun), and a decrease in notifications below the trend in Q3 (Jul-Sep) and less so in Q4 (Oct-Dec), which is aligned with increases in zoonotic notifications in Australia’s hotter and wetter months. Conclusion: The results present zoonotic notifications in Aboriginal and Torres Strait Islander populations over time and highlight potential implications of climate change due to increasing notifications, and increasing temperatures and extreme weather events in recent years. Implications for public health: The findings can inform preventative health approaches for zoonoses in Indigenous populations, with One Health approaches recommended.